William James' Theory of Truth and Its Relevance for Religious Education - Setiawan, Rudi (UIN Sunan Gunung Djati Bandung, 2024)
Religious absolutism is one of the epistemological roots behind various acts of religious intolerance that threaten the order of life in a plural, dynamic, tolerant and inclusive democratic society. This research is a study of philosophical literature that explores the ideas of William James's pragmatic theory of truth and finds its relevance to religious education in order to anticipate symptoms of religious absolutism. James challenged the absolutism of truth that had been maintained for centuries in the Western philosophical tradition. Truth does not lie in ideas or notions, but rather in the process or event of verification and validation of those ideas or notions in experience. He offers a pragmatic concept of truth that takes into account the practical consequences of ideas in experience. For him, truth should be dynamic, open, continuously growing and plural. Inspired by James' ideas, the author conveys the importance of religious truth and religious education interpreted in a more pragmatic framework. Religious truth is not only built from religious dogma or doctrine but is a reflective and dialogical process through the experience of faith, which is formed in relation to other truths. In a contemporary pluralistic society, religious education cannot be reduced to simply teaching religious doctrine or dogma. Religious education needs to be carried out within a pragmatic framework as a form of religious moderation education that pays attention to efforts to develop critical-reflective abilities to grow faith in a sustainable manner, creatively interpreting human experience, as well as forming human ethical character to maintain a harmonious life together.